2009
DOI: 10.1007/s00423-009-0515-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk of death after emergency repair of abdominal wall hernias. Still waiting for improvement

Abstract: Using multivariate logistic regression analysis, probabilities of death after complicated abdominal wall hernia surgery are increased in patients with: age over 70 years, high ASA class, and associated intestinal resection. Guidelines should be developed to improve prognosis in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 28 publications
(36 reference statements)
4
21
0
3
Order By: Relevance
“…The rates of mortality and morbidity have been reported to be approximately 5% and 20%-30%, respectively. [2,[4][5][6] The results obtained in the present study were consistent with the literature showing a mortality rate of 3.1% and a morbidity rate of 14.2%. Many factors affecting mortality and morbidity have been reported.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The rates of mortality and morbidity have been reported to be approximately 5% and 20%-30%, respectively. [2,[4][5][6] The results obtained in the present study were consistent with the literature showing a mortality rate of 3.1% and a morbidity rate of 14.2%. Many factors affecting mortality and morbidity have been reported.…”
Section: Discussionsupporting
confidence: 92%
“…[8,9] Alverez et al [7] reported that postoperative pulmonary and cardiovascular complications were frequently encountered in the elderly, and consequently, the duration of hospital stay was prolonged in such patients. Martínez-Serrano et al [6] stated that advanced age was an effective factor on morbidity and mortality in incarcerated AWH cases. Likewise, in the present study, it was demonstrated that advanced age had a significant effect on morbidity (p<0.001) and mortality (p<0.005).…”
Section: Discussionmentioning
confidence: 99%
“…Martínez-Serrano ve arkadaşlarının [7] çalışmasında acil karın duvarı fıtık ameliyatı yapılan 70 yaş üzerin-deki hastalarda mortalite oranı %4,5 bulunmuştur. Bizim hasta grubumuzda 60 yaş altı hastalarda hiç mortalite görülmezken, 60 yaş üstünde 4 hasta (%5,5) kaybedildi.…”
Section: Discussionunclassified
“…Considering the low risk of incarceration, the high risk of recurrence, and the relevant rate of postoperative pain and discomfort [17], the principal indication for surgical treatment in incisional hernias has to be critically rethought.…”
Section: Discussionmentioning
confidence: 99%